BINTHE BILUHUTA ACCOUNTING: A STUDY OF ISLAMIC ETHNOMETHODOLOGY - Mohamad Anwar Thalib (Jurnal Bisnis dan Akuntansi, 2024)
This research departs from problems regarding adopting and implementing accounting originating from Western countries, which impact the increasingly marginalized accounting practices based on local cultural values. This study uses an Islamic ethnomethodology approach. The study results show that accounting practices are in the form of value-based affection (motoliango) pricing. This value is reflected through the actions of binthe biluhuta sellers who still accept buyers when they buy less than the set selling price. This is driven by a sense of affection between people and the belief that one should not refuse sustenance. The novelty of this research is that it is the first study to uncover accounting practices by binthe biluhuta sellers based on local cultural values. The contribution of this research is the presence of a holistic accounting concept that consists of material, cultural values, and religiosity. This research implies that the value of local wisdom in the form of compassion can be combined with accounting concepts or theories regarding selling prices. The implemented selling price concept can be used by traders with a materialist, humanist, and spiritual spirit when building a business.